2014
DOI: 10.1016/j.celrep.2013.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of POLB Causes Lupus in Mice

Abstract: Summary A replication study of a previous genome-wide association study (GWAS) suggested that a single nucleotide polymorphism (SNP) linked to the POLB gene is associated with systemic lupus erythematosus (SLE). This SNP is correlated with decreased POLB expression (Pol β). To determine if decreased Pol β activity results in SLE, we constructed a mouse model of POLB that encodes an enzyme with slow DNA polymerase activity. Pol β is a key enzyme in the base excision repair (BER) pathway.. We show that mice expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 38 publications
3
64
1
Order By: Relevance
“…The lack of effect of Pol β likely results from the very low APE1 expression in GC B cells, as opposed to our previous interpretation that the BER pathway does not contribute to SSBs needed for A:T mutations (33). By contrast, it has recently been shown that mice expressing a mutant Pol β with very slow polymerization kinetics have increased SHM of the J H4 flank in GC B cells, with the largest effect on transversions at C:G bp (46). Because Pol β interacts with APE1 and XRCC1 during repair of AP sites (31,47), this mutant Pol β might reduce the turnover of APE1, further decreasing the effective APE1 levels and allowing increased access of APE2 to AP sites.…”
Section: Discussioncontrasting
confidence: 49%
“…The lack of effect of Pol β likely results from the very low APE1 expression in GC B cells, as opposed to our previous interpretation that the BER pathway does not contribute to SSBs needed for A:T mutations (33). By contrast, it has recently been shown that mice expressing a mutant Pol β with very slow polymerization kinetics have increased SHM of the J H4 flank in GC B cells, with the largest effect on transversions at C:G bp (46). Because Pol β interacts with APE1 and XRCC1 during repair of AP sites (31,47), this mutant Pol β might reduce the turnover of APE1, further decreasing the effective APE1 levels and allowing increased access of APE2 to AP sites.…”
Section: Discussioncontrasting
confidence: 49%
“…In fact, healthy centenarians have lower serum levels of inflammatory cytokines (Ferrucci et al ., 1999), and proinflammatory molecules such as interleukin-1β (IL-1β), IL-6, and tumor necrosis factor-α (TNF-α) are upregulated in the aged liver (Rikans et al ., 1999). However, SRT1720, an anti-aging SIRT1 activator, suppresses proinflammatory gene expressions in the livers of aged mice fed a standard diet (Mitchell et al ., 2014) as well as a high-fat diet (Minor et al ., 2011). Although the precise mechanism of age-related inflammation remains elusive, it is important to inhibit inflammation to prevent liver aging.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it would be beneficial to identify effective CR mimetics. Resveratrol (Baur et al ., 2006) and SRT1720 (Mitchell et al ., 2014), SIRT1 activators, and rapamycin (Harrison et al ., 2009), a mammalian target of rapamycin (mTOR) inhibitor, have been proposed as candidate CR mimetics. Resveratrol improves survival and decreases age-related changes such as insulin resistance, mitochondrial number, the motor dysfunction, and liver pathology in mice fed a high-calorie diet (Baur et al ., 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autoantibodies have been associated with alterations in somatic hypermutation (SHM), which is mediated by activation-induced cytidine deaminase (AID, encoded by Aicda) expressed in GC B cells (56,57). Moreover, knockin mice carrying a hypomorphic mutation in the BER DNA polymerase β (Pol β) have a dramatically increased frequency of SHM and develop autoimmunity and lupus-like disease (58). As altered AID activity can result in apoptosis of GC B cells, we determined whether loss of NEIL3 affects Aicda expression and the frequency of SHM.…”
Section: Mice Deficient In Neil3 Have Autoantibodies and Are Susceptimentioning
confidence: 99%